Identifying opportunities to bridge disparity gaps in curing childhood cancer in Malawi: Malignancies with excellent curative potential account for the majority of diagnoses. (4th July 2017) - El-Mallawany, Nader Kim; Wasswa, Peter; Mtete, Idah; Mutai, Mercy; Stanley, Christopher C.; Mtunda, Mary; Chasela, Mary; Mpasa, Atupele; Wachepa, Stella; Kamiyango, William; Villiera, Jimmy; Kazembe, Peter N.; et al.
ABSTRACT: The majority of African children with cancer die without access to resources. We describe efforts to build a public treatment program with curative intent for childhood cancer in Lilongwe, Malawi despite severe limitations in diagnostic and therapeutic resources. We retrospectively analyzed a cohort of childhood cancer patients at Kamuzu Central Hospital from 12/2011–6/2013. Consistently available chemotherapeutic agents were limited to cyclophosphamide, vincristine, doxorubicin, bleomycin, methotrexate, and prednisone. Of 258 newly diagnosed childhood malignancies, 17 patients with retinoblastoma were excluded from clinical analyses due to insufficient clinical data. Among the remainder of the cohort ( n = 241), 42% were female with median age 8.4 years (range 0.6–17.9). Forty-six (19%) were HIV-infected (42 Kaposi sarcoma, 3 Burkitt lymphoma, 1 Hodgkin lymphoma). The most common clinical presentations were palpable abdominal mass (41%), peripheral lymphadenopathy (33%), and jaw mass (17%). Nearly two-thirds of total diagnoses were accounted for by Burkitt lymphoma ( n = 74), Kaposi sarcoma ( n = 52), Hodgkin lymphoma ( n = 21), and Wilms tumor ( n = 19). Twelve-month overall survival for these 4 most common diagnoses was 54% (95% confidence interval 46–61) versus 19% (95% confidence interval 11–30) for all other diagnoses (median follow-up 19 months). Treatment-related mortality was highest in patients with non-Wilms solid tumors of the abdomen (48% versus 10% for the overall cohort, p < 0.001), while treatment abandonment was highest in patients with bone and soft-tissue sarcomas (29% versus 14% overall, p = 0.05). Childhood cancers with excellent curative potential accounted for the majority of patients, establishing an opportunity to build treatment programs with curative intent despite severe limitations.